A Criminological Study against Sexual Violence Performed by Normal Men against Women with Disabilities - Nor Samsyudin; Latifah Hanim; Andri Wijaya Laksana (Universitas Islam Sultan Agung, 2022)
This writing aims to examine the criminology of criminal acts of sexual violence perpetrated by normal men on women with disabilities and the countermeasures made by the Jepara Resort Police to tackle these crimes. This research is included in the type of empirical juridical research. Based on the results of the study, it can be concluded that the object of criminology studies includes three things: criminal acts, perpetrators of criminal acts, and public reactions to both. Furthermore, the object of the study was analyzed using criminological theories. Sexual violence was analyzed using differential association theory. The perpetrators of the crime of sexual violence must have committed a crime because of the factors that caused the crime. After knowing these factors, it was studied using the theory of Social Anomalies. Public reaction to criminal acts and perpetrators of sexual violence. First, the community around the perpetrator provides labeling, or social punishment given to the perpetrator. Second, on the other hand, there are still some people who know about this form of crime and care about the existence of the crime of Sexual Violence by creating forums or becoming activists. This community reaction analysis uses Social interactionist theory.